ЕПІСТЕМОЛОГІЯ ФІЛОСОФСЬКО-ПРАВОВИХ ІДЕЙ У ГАЛИЧИНІ В УМОВАХ БЕЗДЕРЖАВНОСТІ - Вовкович, Уляна Володимирівна (SUPREMANCE OF LAW, 2017)
The retrospection of philosophical and legal researches of Ukrainian scientists who lived and created in Galicia at the end of XIX- beginning of XX centuries and also in Vienna and Prague are considered in this artickle. This period is shown not as isolated process from Ukrainian and European processes of development of legal science, but as process which added and developed content by its own intellectual efforts. Modern researchers should pay attention to this content in order to create their own original philosophical and legal view to undistorted philosophical history of national science of this period of Ukrainian history of philosophy of law.
Keywords: sources of Ukrainian law; philosophical and legal ideas; retrospection; epistemology; reflection of traditions